Al-muḥassināt al-lafẓiyyah fī albūm Muṣṭafā ʿĀṭif (Dirāsah taḥlīliyyah balāghiyyah) - Rizky, Alpian; Sudiarti, Sri (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2025)
This study examines al-muḥassināt al-lafẓiyyah (phonetic and verbal rhetorical devices) found in the song album by Muṣṭafā ʿĀṭif. The purpose of this research is to identify words and expressions that possess aesthetic value and rhetorical influence on listeners through the lyrics sung by Muṣṭafā ʿĀṭif. This research employs a qualitative descriptive method. Data were collected using documentation techniques by reviewing, listening to, and analyzing the song lyrics in the album. The data sources consist of two types: online sources, specifically YouTube, and library sources, namely books related to rhetorical and balāghah studies. The findings reveal that the album contains 16 instances of jinās and 61 instances of sajʿ. Among the 16 jinās, 3 are classified as jinās tām within the category of jinās mumāthil, while of the 61 sajʿ, 11 are categorized as sajʿ mutawāzī and the remaining 50 as sajʿ muṭarraf.